Maximização da Reutilização da Água Residuária do Processamento dos Frutos do Cafeeiro: Influências em Características Físico-químicas do Efluente e Qualidade da Bebida do Café - Moreli, Aldemar Polonini (2013)
The post-harvest fruit of the coffee tree wet processing is an important strategy for improving grain quality. Involves 3-5 L of water in peeling fruit and generates that needs proper management to your final destination. The objective of this study was t